Pengaruh Murottal Al-Qur’an terhadap Tingkat Stres pada Mahasiswa Universitas Islam Indonesia - Hazhira Qudsyi (Jurnal Psikologi Islam, 2021)
Stress is a reaction when the interaction between the individual and the environment is assessed as a burden that is felt beyond the ability of the individual. Stress can be experienced by anyone, one student. One therapy to reduce stress that can be done by Muslims with an Islamic approach is psycho-religiousness by listening to the holy verses of the Qur'an or murottal Al-Qur'an. This study aims to determine the effect of giving murottal Al-Qur'an on stress levels in Indonesian Islamic University students. Research participants were students of the Islamic University of Indonesia, male and female, aged 17-25 years, came from all majors, and were not deaf. This study uses an experimental design of one group pretest and posttest design. Research participants were selected by purposive sampling technique. The subjects of this study amounted to 15 participants. The scale used in this study is the DASS Scale (Depression Anxiety Stress Scale) with a total of 42 items with a reliability coefficient of 0.8806. The results showed that there was a decrease in stress levels in students after being given murottal Al - Qur'an. The decrease in stress levels had a significant result, namely p = 0.009 (p < 0.05). The effect size value in the data is -1.60 which is included in the large effect category. Thus, the research hypothesis can be accepted.